Impacto de la autoestima en la calidad de vida relacionada con salud bucal, en niños de 11 a 14 años con maloclusión (2020)
Introduction: The objective of the study was to see the relationship between self-esteem and oral health-related quality of life (OHRQoL) in a sample of children who began orthodontic treatment at dental clinics in the city of Bogotá, Colombia. Materials and methods: correlational study in children aged 11 to 14 years (98 women, 102 men) to whom the questionnaire (CPQ11-14) and the Rosenberg self-esteem scale were applied. Data will be analyzed with SPSS software (version 26, SPSS, Chicago, Illinois). The individuals were classified according to the DAI dental aesthetic index. They were calculated for the total CPQ11-14 and its domains, as well as for the Rosenberg scale, adding the response codes for each element. Data analyzes include descriptive statistics, bivariate analysis, Pearson's correlation tests, and multiple regression models. Results: Children with low self-esteem had greater difficulties for total CPQ11-14 than children with high and medium self-esteem; finding differences in the three self-esteem groups. Children with low self-esteem had the greatest difficulties in the ICD. The combined model explained 18% of the total variance in CPQ11-14. (Adjusted R2 0.18). The explanatory power was highest for the FL domain (adjusted R2 0.24) and the lowest for the OS domain (adjusted R2 0.17). For the explanation of the total CPQ11-14 and for the OS and FL domains, the contribution was mainly attributed to the DAI, being highly significant (P <0.000). For the explanation of the EW and SW domains, the greatest contribution was for AE. Conclusions: self-esteem and malocclusion present a moderate association with the quality of life related to oral health, in children aged 11 to 14 years who seek orthodontic treatment in consultations for the first time